2004
DOI: 10.1161/01.cir.0000129774.09737.5b
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA Reductase Inhibitor Simvastatin Profoundly Improves Survival in a Murine Model of Sepsis

Abstract: Background-HMG-CoA reductase inhibitors, such as simvastatin, have been shown to exhibit pronounced immunomodulatory effects independent of lipid lowering but to date have not been used to treat severe inflammatory disease such as sepsis. We thus approached the question of whether treatment with simvastatin might improve cardiovascular function and survival in sepsis. Methods and Results-Mice treated with simvastatin and rendered septic by cecal ligation and perforation (CLP) show a mean survival time close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
170
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(198 citation statements)
references
References 29 publications
20
170
1
7
Order By: Relevance
“…In a Klebsiella pneumoniae mouse model of pneumonia, lovastatin delayed bacterial clearance and enhanced dissemination (2). In contrast, statins have consistently improved survival in animal and human bacterial sepsis (16,22,83), implying that the beneficial effects of statins may outweigh their potential deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a Klebsiella pneumoniae mouse model of pneumonia, lovastatin delayed bacterial clearance and enhanced dissemination (2). In contrast, statins have consistently improved survival in animal and human bacterial sepsis (16,22,83), implying that the beneficial effects of statins may outweigh their potential deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…The simvastatin-treated animals also did not experience drops in blood pressure or cardiac output while septic. In addition, monocytes obtained from the simvastatintreated mice had significantly reduced adhesion to ECs under physiologic flow conditions compared with those from untreated mice (an effect reversed by mevalonate) (130). A human ex vivo study showed that oxidative stress, known to increase morbidity and mortality in sepsis, may be decreased by simvastatin in patients with sepsis.…”
Section: Abeles and Pillingermentioning
confidence: 94%
“…A recent study demonstrated that simvastatin pretreatment profoundly improves survival in a murine model of sepsis. 8 Another retrospective study showed that statin therapy reduced both overall and attributable mortality in patients with bacteremia. 9 Many cellular and animal models as well as human data suggested a wide variety of mechanisms for these effects.…”
mentioning
confidence: 99%